Evaluasi Dampak Pelaksanaan Program Keluarga Harapan dalam Meningkatkan Kesejahteraan Masyarakat: Studi kasus di Kampung Sidomulyo, Kecamatan Tanjungpinang Timur, Kota Tanjungpinang - Cindy Febriani; Julia Rahmawati; Natalia Anasthasia Silalahi (Social Issues Quarterly, 2022)
The hopeful family program in Kp. Sidumulyo, East Tanjungpinang sub-district, is a good effort to improve the welfare of the beneficiaries of the assistance, as well as to help break the endless chain of poverty in Indonesia. This study was conducted to determine the impact of the implementation of the Family Hope Program in improving the welfare of the community in Kp. Sidumulyo using descriptive qualitative research methods, in which the data were obtained through interviews, document studies, and documentation. The focus of this research refers to the theory according to Anderson which states that policy impact evaluation is divided into 5 dimensions. And based on the results of the research, the Family Hope Program has a positive impact on the survival of the Beneficiary Families (KPM) in Kp. Sidumulyo, but in the distribution of aid there are still problems such as delays in disbursing aid funds and there are still people who can afford but get assistance.